ENTERPRISE ARCHITECTURE TRENDS OVER A DECADE: A BIBLIOMETRIC ANALYSIS - Firmansyah, Albi; Prassida, Grandys Frieska (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Enterprise Architecture (EA) has recently become significantly essential for every organization in ensuring the alignment of information technology implementation with the organization’s strategy and goals. However, its diverse application to organizations can uprise interesting trends that can be reviewed further. Therefore, this research, through a systematic literature review approach, shows the importance of paying attention to the context and scope of EA which has evolved in the last decade. Bibliometric analysis methods are used to show existing correlations, based on journal article data obtained from 2013 to 2023. This research provides a valuable contribution to the development of EA literature by identifying topics that are frequently discussed and those that have the potential to be discussed in the future and who examine them and their relationship to each other. Furthermore, this research can also provide practitioners and stakeholders with a better understanding of the latest EA implementation trends